2011
DOI: 10.4103/1319-3767.74476
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of non-alcoholic fatty liver disease in obese and overweight Egyptian children: Single center study

Abstract: Background/Aim:Pediatric non-alcoholic fatty liver disease (NAFLD) is a global problem which has been increasingly recognized with the dramatic rise in pediatric obesity. The aim of the present study was to identify the clinical, sonographic, and biochemical predictors for NAFLD in obese children.Materials and Methods:Seventy-six children (2-15 years) were included after an informed consent. All were subjected to full anthropometric assessment (including height, weight, body mass index, subscapular skin fold t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Also, there was an increase in the mean serum level of total cholesterol and triglycerides with increasing the degree of hepatic steatosis. This results was in agreement with Sartorio et al [24], El-Karaksy et al [17] and Duarte and Silva study [26], On the other hand, Papandreo et al [22] reported that none of their studied obese children with NAFLD had abnormal lipid profile or liver indices.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Also, there was an increase in the mean serum level of total cholesterol and triglycerides with increasing the degree of hepatic steatosis. This results was in agreement with Sartorio et al [24], El-Karaksy et al [17] and Duarte and Silva study [26], On the other hand, Papandreo et al [22] reported that none of their studied obese children with NAFLD had abnormal lipid profile or liver indices.…”
Section: Discussionsupporting
confidence: 88%
“…Table 2b: Laboratory characteristics of patients and controls (Cont.). An Egyptian study gave the prevalence of NAFLD in 38.5% inobese children and adolescents [17]. Mechanisms behind the reduced BMD in NAFLD are still not completely understood [2].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Lin et al ( 16 ) found that the odds ratio of diagnosing NAFLD with USG increased 1.391 times for each 5 cm increase of WC. In a study conducted by el-Karaksy et al ( 40 ), a relationship between BMI, subscapular thickness, hip circumference, and WHR, metabolic parameters, and hepatic steatosis is reported in 2-15 years old children. As in adult studies, a relationship between WC and NAFLD has been shown in childhood ( 30 , 41 ).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, an impressive 83% of children with NASH have a BMI ≥97th percentile for age and sex . Among the obese, hyperinsulinaemia and/or dyslipidaemia are considered to be strong predictors of NAFLD .…”
Section: Non‐alcoholic Fatty Liver Disease Prevalence and Epidemiologymentioning
confidence: 99%